HUBUNGAN KESIAPSIAGAAN DENGAN TINGKAT KECEMASAN MASYARAKAT DAERAH RAWAN BENCANA BANJIR DI DUSUN NUSUPAN DESA KADOKAN - Tri Rahmawati; Ika Silvitasari (Jurnal Keperawatan Duta Medika, 2022)
Introduction: Disaster events in 2021 have occurred 5,402 disasters and are dominated by wet hydrometeorological disasters as much as 90%. Flood is an event of an area or low land due to an increase in the volume of water. The impact of floods can be reduced by increasing community preparedness in dealing with disasters, floods are a factor causing anxiety for the community, especially those who have been victims. Objectives: This study aims to determine the relationship between preparedness and the level of anxiety of the community in flood-prone areas in the Nusupan Hamlet, Kadokan Village. Methods: Quantitative research with descriptive correlational research design with cross sectional design, the sample taken is 70 respondents with probability sampling technique, namely simple random sampling. The research instrument uses preparedness questionnaires and HARS (Hamilton Anxiety Rating Scale) questionnaires. Data analysis was carried out using the Spearman Rank test Results: The results of statistical tests on respondents showed p value 0.000 <0.05. Conclusions: There is a significant relationship between preparedness and the level of community anxiety in the Nusupan Hamlet, Kadokan Village.